A SWOT-Based Approach to Smartphone Marketing: Insights from Dunia Cell Surabaya - Rika Amalia Putri; Muslichah Erma Widiana; Enny Istanti (Takaza Innovatix Labs Ltd., 2025)
This study analyzes Dunia Cell Surabaya's marketing strategies using a SWOT framework to assess internal and external factors affecting smartphone sales. Employing a qualitative descriptive approach, data were collected through interviews, observation, and documentation, and then analyzed thematically. Results reveal that product diversity, service quality, and employee competence serve as key strengths, while limited digital marketing and high prices are significant weaknesses. Opportunities arise from Indonesia’s stabilizing economy and increasing smartphone adoption, whereas threats include fierce competition and shifting consumer behavior. The SWOT matrix positions Dunia Cell in Quadrant I, indicating a growth-oriented strategy. To sustain competitiveness, the firm should enhance its e-commerce presence, improve pricing strategies, and diversify product offerings. The study contributes to the SME marketing literature by integrating SWOT analysis with insights on digital transformation, offering actionable strategies for retail adaptation in Indonesia’s dynamic smartphone market.